Allosteric Guest Binding in Chiral Zirconium(IV) Double Decker Porphyrin Cages. Issue 4 (5th January 2021) - Bruekers, Jeroen P. J.; Hellinghuizen, Matthijs A.; Vanthuyne, Nicolas; Tinnemans, Paul; Gilissen, Pieter J.; Buma, Wybren Jan; Naubron, Jean‐Valère; Crassous, Jeanne; Elemans, Johannes A. A. W.; Nolte, Roeland J. M.
Abstract: Chiral zirconium(IV) double cage sandwich complex Zr(1)2 has been synthesized in one step from porphyrin cage H2 1. Zr(1)2 was obtained as a racemate, which was resolved by HPLC and the enantiomers were isolated in >99.5 % ee. Their absolute configurations were assigned on the basis of X‐ray crystallography and circular dichroism spectroscopy. Vibrational circular dichroism (VCD) experiments on the enantiomers of Zr(1)2 revealed that the chirality around the zirconium center is propagated throughout the whole cage structure. The axial conformational chirality of the double cage complex displayed a VCD fingerprint similar to the one observed previously for a related chiral cage compound with planar and point chirality. Zr(1)2 shows fluorescence, which is quenched when viologen guests bind in its cavities. The binding of viologen and dihydroxybenzene derivatives in the two cavities of Zr(1)2 occurs with negative allostery, the cooperativity factors α (=4 K2 /K1 ) being as low as 0.0076 for the binding of N, N' ‐dimethylviologen. These allosteric effects are attributed to a pinching of the second cavity as a result of guest binding in the first cavity. Abstract : Starting from achiral porphyrin cage compounds, chiral zirconium(IV) double decker porphyrin cages have been prepared and their enantiomers resolved. The binding of two viologen guests in the double decker porphyrin cages occurs via a strongly negative allosteric effect, resulting in an almost 3 orders of magnitude weaker binding of the second viologen guest compared to that of the first.